1973
DOI: 10.1080/15421407308083054
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Carrier Drift Mobility in Perylene Single Crystals

Abstract: The electron and hole drift mobilities in highly pure perylene single crystals were measured using a conventional time-of-flight method. Observed values were 0.017 f 0.001 cm2/V sec for electrons and 0.02 -& 0.003 cm2/V sec for holes a t room temperature. The mobilities increased with the temperature between 296"-353 O K with an activation energy of 0.20 eV for electrons.Taking a fluctuation of transfer integrals and a stabilization of electron energy due to the excimer-like excess electron state into consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…15 Undoped perylene is also an interesting research target as an intrinsic semiconductor because it was reported that the electron mobility in zone-refined a-phase single crystals of this molecule exceeded 100 cm 2 V À1 s À1 upon cooling the sample temperature below 30 K. 175 On the other hand, a band calculation has predicted a moderate total width (B0.25 eV) of the valence bands of a-perylene, 176 and the hole mobility magnitudes at RT have been reported to be in the order of 10 À3 -10 À1 cm 2 V À1 s À1 . [177][178][179][180][181] Photoelectron spectroscopy measurements on the a-perylene single crystal samples have been attempted since relatively early days. 109,110,182 Recently, Pookpanratana et al conducted ARTOF measurements on the a-perylene single crystals to reveal an absence of the E-K dispersion in any in-plane directions.…”
Section: Resultsmentioning
confidence: 99%
“…15 Undoped perylene is also an interesting research target as an intrinsic semiconductor because it was reported that the electron mobility in zone-refined a-phase single crystals of this molecule exceeded 100 cm 2 V À1 s À1 upon cooling the sample temperature below 30 K. 175 On the other hand, a band calculation has predicted a moderate total width (B0.25 eV) of the valence bands of a-perylene, 176 and the hole mobility magnitudes at RT have been reported to be in the order of 10 À3 -10 À1 cm 2 V À1 s À1 . [177][178][179][180][181] Photoelectron spectroscopy measurements on the a-perylene single crystal samples have been attempted since relatively early days. 109,110,182 Recently, Pookpanratana et al conducted ARTOF measurements on the a-perylene single crystals to reveal an absence of the E-K dispersion in any in-plane directions.…”
Section: Resultsmentioning
confidence: 99%
“…Perylene (C 20 H 12 ) is one of the simple aromatic hydrocarbons and exhibits a high hole mobility in the crystalline state . A crystalline perylene interfacial layer is expected to exhibit high performance in PHJ PSCs due to fewer grain boundaries and low defect and trap densities.…”
mentioning
confidence: 99%
“…Perylene exhibits a high hole mobility in the crystalline state. 13 AFM images of the perylene film are shown in Fig. 3(a).…”
mentioning
confidence: 99%